Assessment of COVID-19-related olfactory dysfunction and its association with psychological, neuropsychiatric, and cognitive symptoms - Jegatheeswaran, Lavandan; Gokani, Shyam Ajay; Luke, Louis; Klyvyte, Gabija; Espehana, Andreas; Garden, Elizabeth Mairenn; Tarantino, Alessia; Al Omari, Basil; Philpott, Carl Martin (Frontiers in Neuroscience, 2023)
Purpose of review To provide a detailed overview of the assessment of COVID-19-related olfactory dysfunction and its association with psychological, neuropsychiatric, and cognitive symptoms. Recent findings COVID-19-related olfactory dysfunction can have a detrimental impact to the quality of life of patients. Prior to the COVID-19 pandemic, olfactory and taste disorders were a common but under-rated, under-researched and under-treated sensory loss. The pandemic has exacerbated the current unmet need for accessing good healthcare for patients living with olfactory disorders and other symptoms secondary to COVID-19. This review thus explores the associations that COVID-19 has with psychological, neuropsychiatric, and cognitive symptoms, and provide a framework and rationale for the assessment of patients presenting with COVID-19 olfactory dysfunction. Summary Acute COVID-19 infection and long COVID is not solely a disease of the respiratory and vascular systems. These two conditions have strong associations with psychological, neuropsychiatric, and cognitive symptoms. A systematic approach with history taking and examination particularly with nasal endoscopy can determine the impact that this has on the patient. Specific olfactory disorder questionnaires can demonstrate the impact on quality of life, while psychophysical testing can objectively assess and monitor olfaction over time. The role of cross-sectional imaging is not yet described for COVID-19-related olfactory dysfunction. Management options are limited to conservative adjunctive measures, with some medical therapies described.